Communicating the potency of tourism: Study case of Wisata Bahari Lamongan - Khitam, Muhammad Chusnul; Suaedi, Falih; Asmorowati, Sulikah (Faculty of Communications Science, Dr. Soetomo University, 2020)
This study aimed to determine the negotiation model and system of tourism partnership between the local government and the private sector to develop the â€œWisata Bahari Lamonganâ€ (WBL). This research used the qualitative method and negotiation theory part of public diplomacy. This research found that the negotiation and collaboration system used was the Public-Private partnership model with a built/operate/transfer (BOT) system. The private sector was allowed to build tourism facilities according to specified specifications. Then, the facility was built and operated by a private party for 25 years. After the period ended, Wisata Bahari Lamongan ownership was transferred to the local government.